(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Non-Governmental Organizations (NGOs) operate in increasingly complex environments characterized by donor dependency, accountability pressures, financial uncertainty, and operational risks, making effective governance and risk management essential for organizational sustainability. Governance accounting practices such as board oversight, internal audit, compliance monitoring, transparency, and accountability structures are expected to strengthen institutional control and support risk management. However, empirical evidence on the relationship between governance accounting and risk management within NGOs in Kenya remains limited. This study examined the relationship between governance accounting practices and risk management among NGOs in Kajiado County, Kenya. A cross-sectional mixed-methods design was adopted, involving 93 respondents drawn from registered NGOs through a census approach. Data were collected using structured questionnaires and key informant interviews and analysed using descriptive statistics, Pearson correlation, and simple linear regression, alongside thematic analysis of qualitative data. The descriptive findings indicated high levels of governance accounting adoption among NGOs, particularly in relation to internal audits and financial controls (M = 4.59, SD = 0.56), compliance with statutory and regulatory requirements (M = 4.55, SD = 0.63), and board oversight structures (M = 4.51, SD = 0.56). Correlation analysis revealed a positive but statistically insignificant relationship between governance accounting and risk management (r = 0.186, p = 0.074). Similarly, regression analysis showed that governance accounting had a positive but statistically insignificant relationship with risk management (β = 0.306, p = 0.074), explaining 3.5% of the variation in risk management outcomes (R² = 0.035). Qualitative findings suggested that governance accounting contributed to institutional stability and accountability but was more effective when embedded in routine organizational decision-making rather than maintained primarily for compliance. The study concludes that governance accounting is an important accountability and control mechanism within NGOs, but its independent contribution to risk management is limited when examined in isolation. The study recommends stronger integration of governance systems into strategic risk oversight, institutional decision-making, and organizational accountability frameworks.